IMPLEMENTATION OF BARIUM ANALYTICAL TECHNIQUE IN WASTEWATER BY ATOMIC ABSORPTION SPECTROMETRY - Camero Jiménez, José W. (2014)
The implementation of a test method ensures the analytical reliability of the test result, reason why the present paper deals with the implementation of the analytical method described in the Standard Methods 3111 D - Direct Nitrous Oxide - Acetylene Flame Method for the determination of barium in the matrix of wastewater, using an atomic absorption spectrometer. It is implementation has the approach of the system of management of quality of testing laboratories ISO/IEC 17025: 2005, being evaluated statistical parameters: accuracy (trueness and precision), method detection limit, quantification limit, working range, linearity, sensitivity and robustness.